Full substitutability - John William Hatfield; Scott Duke Kominers; Alexandru Nichifor; Michael Ostrovsky; Alexander Westkamp (Theoretical Economics, 2019)
Various forms of substitutability are essential for establishing the existence of equilibria and other useful properties in diverse settings such as matching, auctions, and exchange economies with indivisible goods. We extend earlier models' definitions of substitutability to settings in which each agent can be both a buyer in some transactions and a seller in others, and show that all these definitions are equivalent. We then introduce a new class of substitutable preferences that allows us to model intermediaries with production capacity. We also prove that substitutability is preserved under economically important transformations such as trade endowments, mergers, and limited liability.
Keywords: C62; C78; D44; D47; 330; Matching with contracts; substitutability; trading networks